Synthesis, structures, and insulin-like activity of oxidovanadium(V) complexes derived from 2-chloro-N′-(3-ethoxy-2-hydroxybenzylidene)benzohydrazide. Issue 8 (17th April 2016) - You, Zhonglu; Zheng, Boyang; Yang, Ting; Liu, Fang; Cheng, Xiao-Shan
Abstract: Three new oxidovanadium(V) complexes, [VOLL′] (L = 2-chloro- N ′-(3-ethoxy-2hydroxybenzylidene)benzohydrazide, L′ = acetohydroxamate for1, methylmaltolate for2, and ethylmaltolate for3 ), have been prepared. The complexes have been characterized by physicochemical methods and single-crystal X-ray determination. Vanadium in each complex is coordinated by the NOO donor set of L, the OO donor set of L′, and one oxido, forming octahedral coordination. The complexes were administered intragastrically to both normal and alloxan-diabetic mice for two weeks. The biological activities show that the complexes at doses of 10.0 and 20.0 mg V·kg −1 can significantly decrease the blood glucose level in alloxan-diabetic mice, but the blood glucose level in the treated normal mice was not altered. Abstract :